Core Competencies in Geriatric Dentistry Fellowship Programs: a Delphi Study. (11th February 2016) - Hogue, Christie M.; Andrade, Allen D.; Ruiz, Jorge G.; Gibson, Gretchen
ABSTRACT: Purpose/Objectives: The healthcare workforce is challenged with preparing for the increasing number of older persons and complexities of their healthcare needs. Fellowship trained geriatric dentists are charged with the task of addressing the dental needs of this vastly growing cohort.The purpose of this study is to formulate a set of competencies for Geriatric Dental Fellowship Training Programs. Methods: The Delphi technique—a series of three rounds of anonymous questionnaires to obtain the opinions of experts without bringing them together. Results: In Round 1, we proposed 45 competencies based on findings in previous literature. In Round 2, there were 19 respondents whose edits narrowed our list to 39 competencies proposed by the participants. In Round 3, based on group consensus we formulated a final list of 42 competencies. Conclusion: Utilizing the Delphi process, a panel of geriatric dental experts identified a set of core competencies for curriculums in dental fellowship programs.